(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the 15th century, Leonardo da Vinci tried to determine the distance between moving ships by submerging a pipe in water. Such experiments eventually led to the development of a means of detecting the sound of underwater objects (sonar) using acoustic radiation. In the 15th century, Leonardo da Vinci tried to determine the distance between moving ships by submerging a pipe in water. Such experiments eventually led to the development of a means of detecting the sound of underwater objects (sonar) using acoustic radiation.